Development and validation of the methods for determination of tenophovir in the blood plasma of rabbits - Yu. V. Medvedev; G. V. Ramenskaya; I. E. Shokhin; T. A. Yarushok; M. A. Sheveleva (Сеченовский вестник, 2011)
Scribes development and validation of HPLC method with UV detection at 260 nm for determination of tenofovir in rabbit plasma. Plasma samples were treated by protein precipitation using methanol. HPLC analysis was performed on Waters Atlantis T3 column (5 μm, 4,6 x 150 mm), with precolumn Waters Atlantis T3 (5 μm, 4,6 x 20 mm). Acetonitrile –phosphate buﬀer pH 5.70 (16:84) at 1.0 mL/min was used as mobile phase. The standard curve was linear over the range 0.23 μg/ml to 112,98 μg/ml of tenofovir in plasma. Method precision (RSD, %) was 6.08 % to 12.36 % determined on spiked samples. The accuracy of the method (ε, %) was – 2.96 % to 14.55 %. The lower limit of quantiﬁcation was 0.23 μg/ml. The method was applied to preclinical pharmacokinetics study of tenofovir drug products in rabbits.